Parameter theory and linguistic change - Galves, Charlotte (Oxford : Oxford University Press, 2013)
Leading scholars examine languages ranging from old Egyptian to modern Afrikaans. They consider the insights parametric theory offers to understanding the dynamics of language change and test new hypotheses against an extensive array of data.
Series from CIP print record.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Includes bibliographical references and index.
Keywords: Linguistic change; Grammar, Comparative and general -- Syntax; Parameter estimation